2019
DOI: 10.1016/j.ophtha.2019.05.027
|View full text |Cite
|
Sign up to set email alerts
|

Phenotypic Features of Oguchi Disease and Retinitis Pigmentosa in Patients with S-Antigen Mutations

Abstract: To present phenotypic features of 22 patients with S-antigen (SAG) mutations. Design: Retrospective cohort study.Participants: Twenty-one Japanese patients from 16 families with a homozygous c.924delA mutation and 1 patient with a homozygous c.636delT mutation in the SAG gene.Methods: Clinical records on symptoms; best-corrected visual acuity; and Goldmann perimetry, fundus photography, fundus autofluorescence (FAF), OCT, and electroretinography results were reviewed.Main Outcome Measures: Best-corrected visua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
15
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3
3
2

Relationship

3
5

Authors

Journals

citations
Cited by 34 publications
(19 citation statements)
references
References 19 publications
4
15
0
Order By: Relevance
“…Previous studies have revealed that mutations in the Arrestin 1 gene ( Arr 1 , also abbreviated as SAG , soluble antigen) cause Oguchi disease, a type of autosomal recessive “stationary” night blindness [72] or autosomal recessive RP [73]. Recently, Nishiguchi and associates reported that patients with Arr 1 ( SAG ) gene mutations show phenotypic heterogeneity varying from stationary Oguchi type to progressive RP type [74]. Thus, the Arr1 –/– mice can be considered to be a mouse model of RP [75].…”
Section: Animal Models Of Rp and Sd-oct Analysesmentioning
confidence: 99%
“…Previous studies have revealed that mutations in the Arrestin 1 gene ( Arr 1 , also abbreviated as SAG , soluble antigen) cause Oguchi disease, a type of autosomal recessive “stationary” night blindness [72] or autosomal recessive RP [73]. Recently, Nishiguchi and associates reported that patients with Arr 1 ( SAG ) gene mutations show phenotypic heterogeneity varying from stationary Oguchi type to progressive RP type [74]. Thus, the Arr1 –/– mice can be considered to be a mouse model of RP [75].…”
Section: Animal Models Of Rp and Sd-oct Analysesmentioning
confidence: 99%
“…The sequenced reads were aligned to the human reference genome using BWA-mem (ver. Sanger sequencing was carried out for genotyping of family members using the protocol described earlier 45 . In brief, genomic DNA was amplified with PCR using Amplitaq agarose gel with appropriate controls and markers.…”
Section: Wgs and Sanger Sequencingmentioning
confidence: 99%
“…Electrophysiologically there is normal cone function, delayed rod dark adaptation and marked rod desensitization to a bright flash. Most reported cases have this distinctive phenotype and no significant variation in disease expression has been reported, with the exception of a few rare cases (Hayashi et al, 2007; Nishiguchi et al, 2019). Distinguishing between Oguchi disease and other forms of CSNB is important as they may have different prognoses—some patients with Oguchi disease report very slowly progressive visual dysfunction, whereas those with classical CSNB do not.…”
Section: Introductionmentioning
confidence: 99%
“…Electrophysiologically there is normal cone function, delayed rod dark adaptation and marked rod desensitization to a bright flash. Most reported cases have this distinctive phenotype and no significant variation in disease expression has been reported, with the exception of a few rare cases (Hayashi et al, 2007;Nishiguchi et al, 2019). POULTER ET AL.…”
Section: Introductionmentioning
confidence: 99%